Safety of Over-the-Counter Medications in Pregnancy. Issue 4 (July 2019) - Stanley, Angela Y.; Durham, Catherine O.; Sterrett, James J.; Wallace, Jerrol B.
Abstract : Abstract: Approximately 90% of pregnant women use medications while they are pregnant including both over-the-counter (OTC) and prescription medications. Some medications can pose a threat to the pregnant woman and fetus with 10% of all birth defects directly linked to medications taken during pregnancy. Many medications have documented safety for use during pregnancy, but research is limited due to ethical concerns of exposing the fetus to potential risks. Much of the information gleaned about safety in pregnancy is collected from registries, case studies and reports, animal studies, and outcomes management of pregnant women. Common OTC categories of readily accessible medications include antipyretics, analgesics, nonsteroidal anti-inflammatory drugs, nasal topicals, antihistamines, decongestants, expectorants, antacids, antidiarrheal, and topical dermatological medications. We review the safety categories for medications related to pregnancy and provide an overview of OTC medications a pregnant woman may consider for management of common conditions. Abstract : Use of over-the-counter medications during pregnancy and breastfeeding is wide-spread. In this review, details of common medications that are used during pregnancy are covered. Up-to-date information for nurses caring for women during pregnancy and lactation is offered so nurses are prepared to give accurate advice.